Ciężkie i oczywiste przekroczenie granic swobodnego uznania przez instytucje unijne jako przesłanka odpowiedzialności odszkodowawczej UE - Pindel, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In accordance with Article 340 of the Treaty on the Functioning of the European Union TFEU, the EU is obliged to undo any damage caused by its institutions as well as officials, connected with the exercise of public authority. The premises of such responsibility are: wrongful act of the Union, damage and the causal link between this damage and the action of the EU. These principles are common to all Member States.Nonetheless, not every wrongful act leads ad hoc to liability for damages. It is so because a qualified breach of a superior norm conferring rights of individuals in areas where the Union makes economic policy choices so-called Schöppenstedt Formula is needed. According to the already established case law of the Court of Justice, wherever the EU institutions possess wide discretion, the Schöppenstedt Formula has to be used. However, it is applicable only where the Union has a narrow margin of discretion, or does not possess it at all. Additionally, the wrongful act itself is enough to obtain compensation. It should be remembered that the misuse of power does not automatically result in reimbursement of compensation to an individual. In accordance with established case law, initiated in the statement of the ECJ in Bergaderm case, the infringement should have a serious character, because otherwise “the general interest of the Community would be threatened”.
Keywords: odpowiedzialność odszkodowawcza; instytucje unijne; granice swobodnego uznania